式14: "x" Superscript, "x" , Baseline natural log left parenthesis, "x" , right parenthesis minus "x" "x" Superscript, left parenthesis, "x" minus 1 , right parenthesis , Baseline equals 0xxlnx−xxx−1=0
14
2. Substitute y=x
15
式16:
16
式17: "x" Superscript, "x" , Baseline natural log left parenthesis, "x" , right parenthesis minus "x" Superscript, "x" , Baseline equals 0xxlnx−xx=0
17
3. Simplify
18
式19:
19
式20: natural log left parenthesis, "x" , right parenthesis minus 1 equals 0lnx−1=0
20
4. Divide by x^x, because x can't be 0.
21
式22:
22
式23: natural log left parenthesis, "x" , right parenthesis equals 1lnx=1
23
式24: "x" equals "e"x=e
24
Add 1 and solve.
25
式26:
26
式27: "x" equals "y" equals "e"x=y=e
27
x=y, so y also equals e. This means the intersection is at (e,e)